Key parameters of the 2nd flightphase of the tsukahara with salto backward piked - Brehmer, S.; Naundorf, F. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
For a high final score the gymnast need a high difficulty, but this is equivalent to a potential injury risk. Therefor purpose of this study was to identify key parameters of the 2nd flight phase for a safety execution of the Tsukahara with salto backward piked. Nine world class athletes were selected from Videos of two competitions with international participation. Each vault was examined with a 2D kinematic analysis from contact phase of the vaulting table up to the landing. With the help of these evaluated reference values coaches and scientist are able to compare the execution of their gymnasts with the help of a motion analysis to check for their safety and the successful learning of the vault.